2014
DOI: 10.1080/09540121.2014.963007
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of HIV testing in Tanzania to inform future strategies and interventions

Abstract: This study identified characteristics of Tanzanians who have never tested for HIV in order to inform localized interventions to increase HIV testing coverage and uptake. A total of 3257 randomly selected participants aged 18-49 years were surveyed in 16 Mainland regions. Those surveyed were asked about demographics, HIV risk perception, HIV testing behavior, knowledge of both their own and partner's HIV status, and if they were tested with their partner. Approximately 22% of women and 46% of men reported never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…48 Engaging in high-risk sexual practices, including multiple partners and condomless sex, was not associated with recent testing for either gender. This corroborates findings from a study conducted in Tanzania that found no association between risk perception and HIV testing, 49 suggesting people either do not perceive themselves at risk or believe they are at risk but choose not to test. 50 Therefore, communication campaigns aiming to increase HIV testing uptake might be ineffective if messages focus on linking people's sexual history and sexual behaviors to testing.…”
Section: Discussionsupporting
confidence: 88%
“…48 Engaging in high-risk sexual practices, including multiple partners and condomless sex, was not associated with recent testing for either gender. This corroborates findings from a study conducted in Tanzania that found no association between risk perception and HIV testing, 49 suggesting people either do not perceive themselves at risk or believe they are at risk but choose not to test. 50 Therefore, communication campaigns aiming to increase HIV testing uptake might be ineffective if messages focus on linking people's sexual history and sexual behaviors to testing.…”
Section: Discussionsupporting
confidence: 88%
“…HTC not only identifies one’s HIV status, but can also positively influence one’s sexual risk behavior and reduce the likelihood of future HIV acquisition or further transmission [ 6 , 7 ]. Reported socio-demographic factors associated with HTC include older age, marriage, higher educational status, urban residence, higher socio-economic status (SES), and reporting a single partner [ 8 , 9 ]. For youth age 15–24 years, studies have shown pregnancy or ever having made someone pregnant, urban residence, higher education (for men), and a higher frequency of clinic visits are all predictors of HTC among South African youth.…”
Section: Introductionmentioning
confidence: 99%
“…According to their conditions of access and their distribution in the metropolitan cities of Cameroon, there is 22 Accredited HIV/AIDS Treatment Center (AHTC) per region and around 60 Take Care HIV Units (TCHU) in the 10 regions of Cameroon (Far-North, North, Adamoua, Littoral, Center, South, East, West, North-West and South-West). HIV testing activity in the AVCTs shows significant regional and local disparities [7][8][9]. These disparities are partly explained by the situation of the epidemic in each region and are also reflected in the overall screening activity as reported by the analytical laboratories but also in the quality of the care [10][11][12].…”
Section: Introductionmentioning
confidence: 99%